Foundations for Social Entrepreneurship: An Integrative Indian Perspective - Nandram S.S.; Bindlish P.K.; Purohit H.; Joshi A.; Hingorani P. (My University, 2025)
Social entrepreneurship has been positioned as a special form of entrepreneurship and is receiving growing attention from scholars and practitioners. It is relevant to all continents and cultures, but the ways it manifests itself in each continent vary. In this chapter we argue that the fundamental questions about what motivates people to start practicing as social entrepreneurs can be answered by following an integrative paradigm. We distinguish five principles that serve as building blocks for such a paradigm. The first principle is “Respect for Integral Unity”, which refers to the existence of one truth, although conveyed by people in different ways. The second one is “Embodied Knowing”, which refers to experiential knowledge for actions detached from the fruits. The third one is “Holistic Attainment of Life Goals”, which is a situation where people are striving to realize their life goals in a holistic, not piecemeal, way. The fourth one is “All Connectedness”, referring to the belief that we are all connected. The fifth principle is “Doing without Doership”, which is the idea that we are not the doer ourselves but that our actions are the result of the interplay of various aspects of nature. Our analysis shows that these principles raise new questions in the field of social entrepreneurship. Moreover, an integrative paradigm requires an integrative research process. We propose such a process consisting of the following questions: conviction toward knowing what is to be known; what is the object of knowledge; what is the objective of knowing; what is the definition of the thing to be known and how to reach coherent understanding of the phenomenon, taking into account all observations, even if they start from different perspectives. © The Author(s) 2019.